2012
DOI: 10.1371/journal.pone.0033065
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diversity Changes during the Postglacial in East Asia: Insights from Forest Refugia on Halla Volcano, Jeju Island

Abstract: Understanding how past climate changes affected biodiversity is a key issue in contemporary ecology and conservation biology. These diversity changes are, however, difficult to reconstruct from paleoecological sources alone, because macrofossil and pollen records do not provide complete information about species assemblages. Ecologists therefore use information from modern analogues of past communities in order to get a better understanding of past diversity changes. Here we compare plant diversity, species tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Vegetation parameters such as coverage of herb layer, density of trees, as well as the degree of canopy openness, vary altitudinally between habitats (Doležal et al . , Russo et al . , Djuikouo et al .…”
mentioning
confidence: 99%
“…Vegetation parameters such as coverage of herb layer, density of trees, as well as the degree of canopy openness, vary altitudinally between habitats (Doležal et al . , Russo et al . , Djuikouo et al .…”
mentioning
confidence: 99%
“…When considering the geographic distribution of mountain forest types dominated by conifers (types 1.1 and 1.2), we can reasonably assume that during the last glacial maximum there was conifer‐rich vegetation covering the upper parts of mountain ridges on the Korean Peninsula (Igarashi ; Ren & Zhang ; Kong ; Doležal et al. ). During the Holocene warming, plant species retreated to cooler conditions (Ren & Zhang ; Kong ) and the coniferous forests were immigrated with oceanic taxa from both southern and lowland refugia (Yi et al.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be conceived in terms of recent refugia of the main post‐glacial forest types (Doležal et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested Jeju Island to be a crossroad between different plant migration routes (mainly, one from the east—likely from Pacific Japan—and another from the south through land bridges in the ECS; e.g., Dolezal et al, 2012). Postglacial recolonization of mainland Korea from propagules coming from Taiwan (i.e., through this southern route) seems unlikely, as the “white” genetic cluster characterizing this large island is not present in any of the sampled mainland Korean populations (and the UPGMA phenogram also include the Taiwanese populations in a clearly separated cluster).…”
Section: Discussionmentioning
confidence: 99%